Gatekeeper competencies for suicide prevention among Korean social work students: a path model of the relationship between education and gatekeeper intention - Jungyai Ko (Frontiers in Public Health)
PurposeWith the high suicide rate and low utilization of mental health services in Korea, gatekeeping is a crucial public health strategy for suicide prevention. Social workers have the potential to serve as professional gatekeepers in this context. This study examined the relationships between social work students’ educational experiences, suicide prevention competencies, including knowledge, attitudes, and perceived preparedness, and their intentions to perform gatekeeper roles.MethodsThe online survey collected data from 18 randomly selected social work schools across Korea. The final data included 496 social work students (193 in the 3rd and 303 in the 4th year). Path analyses were conducted on a hypothesized path model in which students with more educational experience had higher competencies and stronger intentions for gatekeeper roles. It was also hypothesized that these competencies mediated the relationship between educational experiences and gatekeeper intentions.ResultsThe results demonstrated the validity of the suggested path model (CFI = 0.995, TLI = 0.977, RMSEA = 0.027, SRMR = 0.022). Classroom learning was associated with increased knowledge about suicide (p < 0.05), and field experiences were related to more positive attitudes toward suicide prevention (p < 0.01). Students’ intention to perform gatekeeper roles was predicted by knowledge (p < 0.001), attitudes (p < 0.05), and perceived preparedness (p < 0.001), and indirectly by educational experiences.ConclusionThese findings suggest that university-level education can play a critical role in preparing social work students as professional gatekeepers by providing various educational experiences and enhancing the key competencies needed for suicide prevention. Future studies should consider adopting a longitudinal design to understand the association between education and actual practice behavior.